OP02 Prevalence and severity of nonalcoholic fatty liver disease in a large prospective primary care cohort with abnormal liver function tests. (16th November 2010) - Armstrong, M; Houlihan, D; Bentham, L; Shaw, J; Olliff, S; Neuberger, J; Lilford, R; Newsome, P
Abstract : Introduction: An unexpected finding of abnormal liver function tests (ALFTs) is common in primary care. Currently there is a lack of data for determining the severity of liver disease, in particular nonalcoholic fatty liver disease (NAFLD), in the primary care setting. Aim: To determine the causes of unexpected ALFTs in a large primary care cohort. To determine the prevalence and severity of NAFLD in this cohort. Method: We analysed patients presenting with ALFTs, in the absence of known liver disease, to 8 primary care practices in Birmingham between 2006 and 2008. NAFLD was diagnosed in subjects with fatty liver on ultrasound (USS), negative liver aetiology screen, and alcohol consumption of =21 & =14 units/week in males and females, respectively. As a sub-study we calculated the NAFLD Fibrosis Score (NFS) (Angulo, Hepatology 2007) to estimate the presence of advanced liver fibrosis (F3/F4 Kleiner classification) in subjects who met the diagnostic criteria for NAFLD. Results: Data from 1118 adult patients were analysed: 56% male; 83.9% white race; Age 60 years (48–70); 23.5% type 2 diabetes; 52.2% hypertension; body mass index 28.7 kg/m 2 (25.5–33.1) (values expressed as median (IQR) or %). Regarding alcohol consumption, 42.5% were non-drinkers, 32.2% drank within UK guidelines (male=21, female=14 units/week) and 26.3% drank in excess. Liver aetiologies identified included alcohol-induced liver disease (25.7%), haemochromatosis/carrier (1.1%), viral hepatitis B/C (0.91%), primary biliary cirrhosis (0.8%), alpha-1-antitryspin deficiency (0.18%) and primary sclerosing cholangitis (0.18%). Aetiology remained unexplained (normal USS, negative liver aetiology screen and alcohol consumption within UK guidelines) in 479 subjects, although at least 18% of this group had 2+ factors of the metabolic syndrome. NAFLD was diagnosed in 26.4% (295/1118) of cases. A high NFS (>0.676) was found in 7.6% of these cases indicating the presence of advanced liver fibrosis. The presence of advanced fibrosis could not be confidently excluded in 35.2% of NAFLD patients who had an "indeterminate" NFS (−1.455 to 0.676), indicating the need for further investigation. Although NFS was validated in a secondary care cohort and may over-read severity in primary care, it is currently the best validated non-invasive method of assessing liver fibrosis in patients with NAFLD. Conclusion: NAFLD accounts for over a quarter of patients with ALFTs in primary care (26.9%). Of the patients with NAFLD a significant proportion either have advanced fibrosis (7.6%) or require further investigation (35.2%). This highlights the growing burden of NAFLD, and the need for validated methods of assessing NAFLD disease severity in primary care.